Activities and Achievement of Targets in Care Services and Programs at The Elementary School UKGS Banyumanik The District of Semarang - Sariyem Sariyem; Sadimin Sadimin; Bambang Sutomo (Jurnal Riset Kesehatan, 2014)
The purpose of this research is to know what types of activities and targets of achievement in Care services and UKGS programs at the elementary schools in Banyumanik Semarang. Qualitative methods are used to explore about activities that are already implemented in the UKGS program and care services and look at the factors that inhibit the activity. The result shows that UKGS program has been conducted in accordance with the curriculum materials that incorporate oral health, the program managers also conduct sessions of information on oral health but is not optimal yet. Common disease prevention is still implemented, curative measures were undertaken for students who require care service. They still lack of medical officer, facilities, infrastructures, closest health center. Almost all activities except gargle with fluorine have been carried out. Thus, some efforts are made on the activities of care services. Supporting Factors like the officer always must be be in place ready if needed, so that existing activities within care services can all be resolved. It also helps health centers in health care in the elementary school. Barrier that exists is the school is not allowed to collect fees from parents.